2021
DOI: 10.15252/embj.2019103811
|View full text |Cite
|
Sign up to set email alerts
|

A weakened interface in the P182L variant of HSP27 associated with severe Charcot‐Marie‐Tooth neuropathy causes aberrant binding to interacting proteins

Abstract: HSP27 is a human molecular chaperone that forms large, dynamic oligomers and functions in many aspects of cellular homeostasis. Mutations in HSP27 cause Charcot‐Marie‐Tooth (CMT) disease, the most common inherited disorder of the peripheral nervous system. A particularly severe form of CMT disease is triggered by the P182L mutation in the highly conserved IxI/V motif of the disordered C‐terminal region, which interacts weakly with the structured core domain of HSP27. Here, we observed that the P182L mutation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 124 publications
(216 reference statements)
1
29
0
Order By: Relevance
“…A second example of a gene-specific phenotype is the formation of HSPB1-positive aggregates due to C-terminal HSPB1 mutations. 21 We validated the presence of HSPB1 aggregates in our iPSC-derived motor neurons from the HSPB1 P182L line, using immunostaining at Day 37 for HSPB1 ( Supplementary Fig. 3 A).…”
Section: Resultsmentioning
confidence: 86%
“…A second example of a gene-specific phenotype is the formation of HSPB1-positive aggregates due to C-terminal HSPB1 mutations. 21 We validated the presence of HSPB1 aggregates in our iPSC-derived motor neurons from the HSPB1 P182L line, using immunostaining at Day 37 for HSPB1 ( Supplementary Fig. 3 A).…”
Section: Resultsmentioning
confidence: 86%
“…Since the major aspect regulating HSPB1 activity relies on its self-association and dissociation, dimerization and oligomerization dynamics have been investigated as one of the primary features possibly altered in the mutant protein. In vitro, biochemical studies on HSPB1 mutations falling in different regions of the protein sequence revealed a common tendency to form larger oligomers, often accompanied by a decreased chaperone activity in respect to the HSPB1 wild-type (WT); in vitro analyses also reported a destabilization of the quaternary structure of mutated HSPB1 (Nefedova et al, 2013a;Nefedova et al, 2013b;Chalova et al, 2014b;Muranova et al, 2015;Alderson et al, 2021). Clustering HSPB1 mutations through a domain-dysfunction linkage is not unequivocal, due to contrasting observations resulted from different techniques and assays used to study mutations localized in the same HSPB1 region (Almeida-Souza et al, 2010;Ylikallio et al, 2015;Echaniz-Laguna et al, 2017a).…”
Section: Hspb1mentioning
confidence: 99%
“…Another structurally notable feature of the ACD is the β4/β8 groove which includes a hydrophobic pocket centered between β-strands 4 and 8 and is located on the outer edge of the ACD β-sandwich (Ehrnsperger et al, 1997 ; Klevit, 2020 ; Reid Alderson et al, 2021 ; Figure 3C ). Therefore, within a dimer of Hsp27 there are two hydrophobic grooves located at the edges of each monomer and one shared dimer interface groove created by the linkage of two monomers (Clouser et al, 2019 ; Boelens, 2020 ; Figure 3D ).…”
Section: Introductionmentioning
confidence: 99%
“…This is described as an extended formation of the CTR in the trans-conformation as the canonical proline can undergo cis-trans isomerization about the I-P peptide bond (Alderson et al, 2017 ). The interaction is found to occur within the same dimeric subunit and between adjacent dimers as well (Reid Alderson et al, 2021 ). The lowly populated residual β-strand structure may further encourage binding between the ACD and CTR and other binding partners (Alderson et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation